Reduction of JITANTI PTM Questionnaire: Principal Component Factor Analysis - Suprajitno Suprajitno; Sri Mugianti; Bastianus Doddy Riyadi; Juin Hadi Suyitno; Puguh Yudho Trisnanto (STIKes Patria Husada Blitar, 2023)
69 questions in the JITANTI PTM application with the logo , can be employed to measure an individual's risk of suffering from non-communicable diseases. The 69 questions in the app can tire the user's eyes, as can the app user's comments. The objective of the study is to reduce questions in order to be more effective. The research design used was cross-sectional. The sample who volunteered to fill out the JITANTI PTM application were 324 people using simple random sampling. The inclusion criteria was people who were living in Blitar Raya, at risk of suffering from non-communicable diseases, and frequently consuming fast food and drinks. Data collection was administered from April to June 2022. Data analysis was then performed to calculate validity using Pearson Product Moment, reliability by administering Cronbach's a, and factor loading employing principal component factor analysis. The software for calculations utilized SPSS. The validity test values obtained were between 0.234 – 0.708 which is greater than r table at a = 0.05 and degrees of freedom > 300 = 0.113, meaning the questions met the validity requirements. The reliability test scores obtained were between 0.783 – 0.907 which met the minimum reliability requirements of 0.7. Based on the Eigenvalue, which is more than 1.0, 19 new questions can be generated (7 for knowledge, 7 for attitude, and 5 for action). Reducing the number of questions in the JITANTI PTM application can reduce user visual fatigue and speed up charging time, thereby reducing the accommodation power of vision.